Occupational impact of internet‐delivered cognitive behaviour therapy for depression and anxiety: reanalysis of data from five Australian randomised controlled trials. Issue 7 (6th October 2014) - Mackenzie, Anna; Harvey, Samuel; Mewton, Louise; Andrews, Gavin
Abstract: Objective: To determine whether internet‐delivered cognitive behaviour therapy (iCBT) for depression and anxiety reduces self‐reported absenteeism in employed individuals. Design, participants and setting : We reanalysed data from five randomised controlled trials of iCBT: two for depression (conducted from September 2008 to February 2009 and from June 2009 to January 2010), two for generalised anxiety disorder (conducted from March 2009 to June 2009 and from July 2009 to January 2010) and one for social phobia (conducted from May 2008 to July 2008). Participants across Australia were recruited via a website. The inclusion criteria were: (i) meets criteria for the disorder of interest; (ii) aged 18 years or over; (iii) no previous history of a psychotic disorder or drug or alcohol misuse; (iv) not actively suicidal. The iCBT courses each consisted of six online lessons (to be completed within 11 weeks), homework assignments, automatic emails and resource documents. Main outcome measure: The number of days absent (self‐reported absenteeism) in the previous week. Results: We included 284 participants in our analysis. When data for the three disorders were combined, participants who received iCBT had significant reductions in self‐reported absenteeism compared with those in the control groups (who were on a waitlist) ( P = 0.03). When data for the three disorders were analysed separately, reductions in self‐reported absenteeism for participants who received iCBT were not significantly different to those for participants in the control groups. Conclusion: Using data from five RCTs, we showed that iCBT was associated with reductions in self‐reported absenteeism. Future research should focus on replicating these findings in other contexts, such as other disorders and other iCBT courses.